Using Standard Division to Solve Multi- Objective Quadratic Fractional Programming Problems - Sulaiman, Nejmaddin A.; Nawkhas, Maher A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
In this paper, Standard Division (SD) technique is used to solve multi-objective Quadratic fractional programming problems (MOQFPP), each objective functions has the following form max.(min.)z=(a_1^t x+α)(a_2^t x+β)/(b_1^t x+γ)(b_2^t x+δ) , and an algorithm suggested for it. Also the problems solved by Chandra Sen technique. We test several examples but introduce two of them in this paper and compare the objective functions between SD and Sen’s technique which is indicate SD technique batter than the other.
Keywords: Standard Division,Chandra Sen,MOQFPP